Deuterated fluorenyl blue-light polymer material and preparation method of film containing planarized conformation

By introducing deuteration treatment into the polyfluorene polymer material, the poly4-alkoxy-9,9-diphenylfluorene polymer luminescent material with the main chain was prepared, which solved the problem of high planarization conformation and inter-chain aggregation of the material during the annealing process, and achieved higher stability and luminous efficiency.

CN119505183AActive Publication Date: 2025-02-25SUN YAT SEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411560714.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing polyfluorene polymer materials produce high planar conformational content and strong inter-chain aggregation during the annealing process, resulting in a decrease in blue light purity and fluorescence quantum efficiency.

Method used

Deuterated 2,7-dibromo-9-fluorenone was synthesized by a one-step method using heavy water as the deuterium source to prepare a poly4-alkoxy-9,9-diphenylfluorenone with the backbone perdeuterated poly4-alkoxy-9,9-diphenylfluorenyl polymer luminescent material (d15-PODPF) to promote the formation of coplanar conformation.

Benefits of technology

It improves the stability and luminous efficiency of the material, enhances the color purity of blue light emission, extends the service life of optoelectronic devices, and simplifies the synthesis process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505183A_ABST
    Figure CN119505183A_ABST
Patent Text Reader

Abstract

The invention provides a deuterated fluorenyl blue-light polymer material and a preparation method of a film containing planarized conformation. In order to solve the problem that the stability of a PODPF material is insufficient, silver carbonate is used as a catalyst, heavy water is used as a deuterium source, and 2, 7-dibromo-9-fluorenone is deoxidized to directly synthesize a deuterated raw material by an H / D exchange one-step method, so that the problem of multiple deuterated synthesis steps is solved, and a novel main chain fully-deuterated poly 4-alkoxy-9, 9-diphenylfluorene polymer luminescent material (d15-PODPF) is prepared. The material can be used for preparing a planarization conformation film, and the problem that the blue light color purity and the fluorescence quantum efficiency are reduced due to the high planarization conformation content and the strong interchain aggregation effect generated by PODPF annealing is solved. The invention also provides the deuterated fluorenyl blue-light polymer material, the planarized conformation film and application of the planarized conformation film in organic film photoelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optoelectronic polymer materials, and in particular relates to a deuterated fluorene-based blue light polymer material and a preparation method of a planar conformation film containing the same. Background Art

[0002] In recent years, the stability of blue light emission has been one of the hot topics in the research of organic thin-film optoelectronic devices. In order to solve this problem, researchers have proposed a variety of solutions, among which the strategy of introducing deuterium has gradually attracted attention. Deuterium (D), as a stable isotope of hydrogen (H), has been widely studied for its application in medicinal chemistry. At the end of 2021, LG Display used deuterated blue light materials to increase the brightness of the panel, and used the "heavy atom effect" to enhance the spin-orbit coupling of the luminescent molecules, significantly improving the quantum efficiency. At the same time, the shorter bond length and larger bond energy of the CD bond reduce the energy of the luminescent material, thereby improving the stability and service life of the device.

[0003] Among many luminescent materials, polyfluorene polymer has become the blue light polymer with the most practical application potential due to its excellent deep blue light emission, high fluorescence efficiency and easy modification. The main chain of polyfluorene is composed of a conjugated skeleton composed of carbon and hydrogen, showing a wide band gap structure. It can not only effectively emit deep blue light, but also has a certain mechanical flexibility, making it a promising blue light semiconductor material. Previous studies have shown that inducing the polyfluorene main chain to form a coplanar conformation can significantly improve the performance and spectral stability of electroluminescent devices.

[0004] Although some progress has been made in improving the luminous efficiency and color purity of polyfluorene materials, there are still some technical problems. For example, the stability of the PODPF material itself is insufficient, and the purity of the device's luminescent color needs to be improved. The existence of these problems limits its performance in practical applications, so further research is needed to optimize the synthesis and performance of polyfluorene polymer materials, thereby improving the overall performance of organic thin-film optoelectronic devices. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a method for preparing a deuterated fluorene-based blue light polymer material, which solves the problem of high planar conformation content generated by PODPF annealing and strong interchain aggregation, which reduces the blue light color purity and fluorescence quantum efficiency.

[0006] The invention also provides a deuterated fluorene-based blue light polymer material.

[0007] The present invention also provides a planarized conformational film.

[0008] The invention also provides a method for preparing the planar conformation film.

[0009] The invention also provides an application of the planar conformation film in an organic thin film photoelectric device.

[0010] The first aspect of the present invention provides a method for preparing a deuterated fluorene-based blue light-emitting polymer material, comprising the following steps:

[0011] S1: Deuterated 2,7-dibromo-9-fluorenone was prepared using 2,7-dibromo-9-fluorenone as raw material, silver carbonate and cyclohexyldiphenylphosphine as catalysts, and heavy water as a deuterium source;

[0012] S2: Preparation of deuterated 2,7-dibromolactone from deuterated 2,7-dibromo-9-fluorenone via Bayer-Villiger rearrangement reaction;

[0013] S3: Deuterated 2,7-dibromodiol was prepared from deuterated 2,7-dibromolactone by Grignard reaction;

[0014] S4: Deuterated 2,7-dibromodiol reacts with 1-bromooctane to undergo an alkyl substitution reaction at the 4-position alcohol hydroxyl group to obtain an oily transparent solid product;

[0015] S5: using the oily transparent solid product as a raw material, preparing a deuterated PODPF monomer;

[0016] S6: preparing the deuterated PODPF monomer into a solution, performing polymerization reaction, activating and refluxing to obtain the deuterated fluorene-based blue light polymer material.

[0017] The present invention relates to a technical solution in a method for preparing a deuterated fluorene-based blue light polymer material, which at least has the following characteristics:

[0018] Beneficial effects:

[0019] In view of the problem that the stability of the PODPF material itself is insufficient and the purity of the device luminescent color needs to be improved urgently, the present invention first uses silver carbonate as a catalyst and heavy water as a deuterium source to deoxygenate 2,7-dibromo-9-fluorenone and directly exchange H / D in one step to synthesize the deuterated raw material, which solves the problem of many steps in deuterated synthesis and prepares a new main chain fully deuterated poly 4-alkoxy-9,9-diphenylfluorene polymer luminescent material (d 15 -PODPF), which can be used to prepare planar conformation films, solving the problems of high planar conformation content generated by PODPF annealing and strong interchain aggregation that reduce the blue light color purity and fluorescence quantum efficiency.

[0020] Deuterated fluorene-based blue light polymer material is a conjugated structure with a fully deuterated main chain.

[0021] According to some embodiments of the present invention, in step S1:

[0022] The CAS number of cyclohexyldiphenylphosphine is 6372-42-5.

[0023] Deuterated 2,7-dibromo-9-fluorenone was prepared in a borosilicate glass tube equipped with a magnetic stir bar.

[0024] The preparation process can be repeated multiple times, such as 3 times, and the deuteration rate is about 93%.

[0025] The raw material input in the deuteration reaction can be 1 mmol, and the reaction is repeated three times.

[0026] The preparation method in step S1 adopts Yamamoto reaction.

[0027] Acetone was used as the solvent for polymer purification.

[0028] According to some embodiments of the present invention, in step S2, trifluoroacetic acid and sodium percarbonate are added during the Bayer-Villiger rearrangement reaction.

[0029] According to some embodiments of the present invention, in step S2, the Baeyer-Villiger rearrangement reaction is performed at room temperature.

[0030] According to some embodiments of the present invention, in step S2, the time of the Bayer-Villiger rearrangement reaction is 60 to 80 hours.

[0031] According to some embodiments of the present invention, in step S2, the time of the Bayer-Villiger rearrangement reaction is 70 to 80 hours.

[0032] According to some embodiments of the present invention, in step S2, the time of the Bayer-Villiger rearrangement reaction is 72 hours.

[0033] According to some embodiments of the present invention, in step S3, the solvent of the grout reaction includes toluene.

[0034] According to some embodiments of the present invention, in step S3, the format reaction is performed under a protective atmosphere.

[0035] According to some embodiments of the present invention, in step S3, the protective atmosphere includes nitrogen.

[0036] According to some embodiments of the present invention, in step S3, the reaction temperature is 80-90°C.

[0037] According to some embodiments of the present invention, in step S3, the reaction temperature is 85°C.

[0038] According to some embodiments of the present invention, in step S3, the reaction time is 20 h to 30 h.

[0039] According to some embodiments of the present invention, in step S3, the reaction time is 24 hours.

[0040] According to some embodiments of the present invention, in step S3, the amount of the Grignard reagent added in the Grignard reaction is 4 to 6 times the equivalent of deuterated 2,7-dibromolactone.

[0041] According to some embodiments of the present invention, in step S4, the alkyl substitution reaction is carried out under alkaline conditions.

[0042] According to some embodiments of the present invention, in step S4, the solvent for the alkyl substitution reaction is acetone.

[0043] According to some embodiments of the present invention, in step S4, the amount of 1-bromooctane added is 1 to 2 times the equivalent of the deuterated 2,7-dibromodiol.

[0044] According to some embodiments of the present invention, in step S4, the amount of 1-bromooctane added is 1.5 times the equivalent of the deuterated 2,7-dibromodiol.

[0045] In the present invention, 1-bromooctane is added, and the corresponding structure is a straight chain. If it is a branched chain, it is impossible to regulate the planar conformation. The branched chain structure can only regulate the spherulite structure (tertiary structure). However, the present invention regulates the planar conformation, that is, the secondary structure.

[0046] According to some embodiments of the present invention, in step S4, the alkyl substitution reaction is performed at room temperature.

[0047] According to some embodiments of the present invention, in step S4, the alkyl substitution reaction time is 20 to 30 hours.

[0048] According to some embodiments of the present invention, in step S4, the alkyl substitution reaction time is 24 hours.

[0049] According to some embodiments of the present invention, in step S5, a deuterated PODPF monomer is prepared by Friedel-Crafts reaction.

[0050] According to some embodiments of the present invention, in step S5, the deuterated PODPF monomer is prepared by Friedel-Crafts reaction, and the specific process is that the product of the previous step is dissolved in anhydrous dichloromethane and reacted under boron trifluoride-ether catalysis conditions for 2 hours to obtain the obtained product.

[0051] According to some embodiments of the present invention, in step S6, the specific process may be:

[0052] Take equal amounts of bipyridine and nickel catalyst Ni(COD)2 in a Shrek flask filled with N2, then activate in a DMF solution at 75°C for 20 minutes, then add a monomer solution dissolved in toluene, reflux at 85°C for 3 days, then cap with 0.1mL dry deuterated bromobenzene, and use a silicon-based metal remover to remove residual nickel catalyst in the post-treatment process. Use DCM as the mobile phase and purify the organic phase with Al2O3 column chromatography, then concentrate the reaction solution, precipitate with anhydrous methanol, and finally use acetone Soxhlet extraction and washing for 3 days to obtain a polymer, which is then vacuum dried to obtain d 15 -PODPF yellow solid is deuterated poly 4-alkoxy-9,9-diphenylfluorene polymer luminescent material (M n =31747, n=69).

[0053] Among them, equal amounts of bipyridine and nickel catalyst Ni(COD)2 are used as catalysts.

[0054] According to some embodiments of the present invention, in step S6, the reaction time is 1.5 to 4 hours.

[0055] According to some embodiments of the present invention, in step S6, activation is performed in a DMF solution.

[0056] According to some embodiments of the present invention, in step S6, a monomer solution dissolved in toluene is added during reflux.

[0057] According to some embodiments of the present invention, in step S6, the reaction mixture is capped with dry deuterated bromobenzene after reflux.

[0058] The second aspect of the present invention provides a deuterated fluorene-based blue light polymer material, which is prepared by the preparation method of the first aspect of the present invention.

[0059] One of the technical solutions of the present invention regarding the deuterated fluorene-based blue light polymer material has at least the following characteristics:

[0060] Beneficial effects:

[0061] Better stability: The CD bond of deuterated materials has higher stability than the CH bond, which reduces the risk of degradation of the luminescent material during operation, thereby extending the service life of the optoelectronic device.

[0062] Higher luminescence efficiency: Enhancing spin-orbit coupling through the "heavy atom effect" helps to improve the quantum efficiency of the luminescent molecules, thereby improving the overall light output of the device.

[0063] Better spectral purity: Deuteration treatment can reduce non-radiative deactivation pathways in luminescent materials, improve the color purity of blue light emission, and ensure that the device can emit more accurate blue light.

[0064] A more simplified synthesis process: heavy water is used as the deuterium source, and the deuterated raw material is synthesized in a one-step method, which simplifies the synthesis steps, reduces production costs and time, and improves synthesis efficiency.

[0065] Can promote coplanar conformation: The prepared deuterated PODPF material can effectively promote the formation of coplanar conformation, enhance the electroluminescent properties of the material, and reduce the spectral drift caused by interchain aggregation.

[0066] Able to enhance mechanical flexibility: The conjugated skeleton structure of polyfluorene material gives it good mechanical flexibility, making the prepared film have better adaptability and durability in practical applications.

[0067] The third aspect of the present invention provides a planar conformation film, and the raw materials for preparing the film include the deuterated fluorene-based blue light polymer material according to the second aspect of the present invention.

[0068] One of the technical solutions of the present invention regarding the planar conformational film has at least the following beneficial effects:

[0069] The planar conformation film containing deuterated fluorene-based blue light polymer material has many beneficial effects, mainly including:

[0070] The planar conformation helps to improve the electroluminescence efficiency of the material, reduce interchain aggregation and non-radiative energy loss, and thus increase the luminescence intensity and quantum efficiency.

[0071] The film exhibits improved spectral stability under light and heat environments, ensuring consistency of spectral characteristics over long-term use.

[0072] The use of deuterated materials reduces the generation of impurities during the light-emitting process and improves the color purity of blue light emission, meeting the requirements of high-quality displays and lighting equipment.

[0073] Due to the conjugated structure of polyfluorene, the film has a certain mechanical flexibility and is suitable for applications in various flexible electronic devices.

[0074] The planarized conformation can be achieved at a lower annealing temperature, which reduces the thermal impact on the substrate and is suitable for the processing of heat-sensitive materials.

[0075] The thin film material of the present invention can be prepared by a simple solution method, the process is relatively simple, and it is convenient for large-scale production.

[0076] Due to its excellent optoelectronic properties, this thin film material can be widely used in organic light-emitting diodes (OLEDs), solar cells and other optoelectronic devices.

[0077] The fourth aspect of the present invention provides a method for preparing the planar conformation film of the third aspect of the present invention, comprising the steps of coating a solution containing the deuterated fluorene-based blue light polymer material on a substrate surface and then annealing.

[0078] A technical solution in the method for preparing a planar conformation film of the present invention has at least the following beneficial effects:

[0079] By directly coating the deuterated fluorene-based blue light polymer material solution on the surface of the substrate, the complicated processing steps are reduced and the production efficiency is improved.

[0080] The coating process can form a uniform film, improve the performance consistency of optoelectronic devices, and ensure that the light-emitting properties are evenly distributed across the film.

[0081] The annealing process can promote the rearrangement of the molecular chains, making them more planar, thereby improving the electroluminescent performance and stability.

[0082] Annealing helps to remove solvent residues, improve the overall density of the film, and enhance its spectral stability under working conditions.

[0083] According to some embodiments of the present invention, the method for preparing a planar conformational film may be:

[0084] Weigh different masses of polymer powder, place in a 1.5 mL clean sample bottle, add 1 mL of solvent, stir at 60 ° C for 30 min, wait for the polymer powder to completely dissolve, and obtain polymer chloroform solutions of different concentrations;

[0085] A quartz plate with a side length of 1.5 cm is used as a substrate. The quartz base is first cleaned with solvents such as acetone and dichloromethane. 45 microliters of polymer chloroform solution is taken and evenly coated on the quartz substrate using a spin coater (or doctor blade) to obtain a thin film for preparing a planar conformation.

[0086] The above-mentioned film is placed on a heating table. The original film is placed on a heating table. By adjusting the annealing temperature (higher than 200° C.), a series of planar conformation films with different contents can be obtained.

[0087] In the method for preparing a planar conformation film, the thermal annealing temperature is 180°C to 340°C.

[0088] In the method for preparing a planar conformation film, the thermal annealing temperature is 200°C to 280°C.

[0089] The fifth aspect of the present invention provides use of the planarized conformational thin film according to the fourth aspect of the present invention in an organic thin film optoelectronic device.

[0090] Applying the planar conformation film prepared from deuterated fluorene-based blue light polymer materials to organic thin film optoelectronic devices can bring the following beneficial effects:

[0091] Improved luminescence efficiency: Since the planar conformation reduces interchain aggregation and non-radiative energy loss, it can significantly increase the luminescence intensity and quantum efficiency in organic light-emitting diodes (OLEDs), thereby improving the overall optoelectronic performance.

[0092] Enhanced spectral stability: The film exhibits good spectral stability under light and heat environments, which helps maintain the consistency of the spectral characteristics of the device over a long period of time, ensuring display quality and service life.

[0093] Improve color purity: The introduction of deuterated materials reduces the generation of impurities during the light-emitting process and improves the color purity of blue light emission, meeting the requirements of high-quality displays and lighting equipment and ensuring accurate color reproduction.

[0094] Mechanical flexibility: The conjugated structure of polyfluorene gives the film a certain mechanical flexibility, making it suitable for use in various flexible electronic devices, expanding its application range.

[0095] Low temperature processing adaptability: The planarized conformation can be achieved at a lower annealing temperature, which reduces the thermal impact on the substrate, is suitable for the processing of heat-sensitive materials, and expands the types of compatible substrates.

[0096] Simplified preparation process: The film is prepared by a simple solution method, which has a relatively simple process and is easy to mass produce, reducing production costs and time.

[0097] Potential for wide application: Due to its excellent optoelectronic properties, this thin film material can be widely used in OLED, solar cells and other optoelectronic devices, promoting the advancement of related technologies and market applications.

[0098] According to some embodiments of the present invention, the organic thin film optoelectronic device includes an organic light emitting diode, an organic field effect transistor, an organic thin film laser, and an organic spin valve. BRIEF DESCRIPTION OF THE DRAWINGS

[0099] Figure 1 The UV-visible absorption spectra and fluorescence emission spectra of the original fluorene-based polymer films obtained in Example 1 and Comparative Example 1 of the present invention and after heat treatment.

[0100] Figure 2 These are the UV-visible absorption spectra and fluorescence emission spectra of the original fluorene-based polymer films obtained in Example 2 and Comparative Example 2 of the present invention and after heat treatment.

[0101] Figure 3 These are the UV-visible absorption spectra and fluorescence emission spectra of the original fluorene-based polymer films obtained in Example 3 and Comparative Example 3 of the present invention and after heat treatment.

[0102] Figure 4 It is a lifespan diagram of the original fluorene-based polymer film obtained in Example 123 of the present invention and Comparative Example 123 and after heat treatment.

[0103] Figure 5 It is a structural diagram of the fluorene-based polymer thin film device with a planar conformation obtained in Example 1 of the present invention and Comparative Example 1.

[0104] Figure 6 It is a performance diagram of the fluorene-based polymer thin film device with a planar conformation obtained in Example 1 of the present invention and Comparative Example 1.

[0105] Figure 7 This is the hydrogen NMR spectrum of the polymer synthesized in Example 1 of the present invention.

[0106] Figure 8 This is the GPC test of the polymer synthesized in Example 1 of the present invention. DETAILED DESCRIPTION

[0107] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0108] In a first aspect, some embodiments of the present invention provide a method for preparing a deuterated fluorene-based blue light-emitting polymer material, comprising the following steps:

[0109] S1: Deuterated 2,7-dibromo-9-fluorenone was prepared using 2,7-dibromo-9-fluorenone as raw material, silver carbonate and cyclohexyldiphenylphosphine as catalysts, and heavy water as a deuterium source;

[0110] S2: Preparation of deuterated 2,7-dibromolactone from deuterated 2,7-dibromo-9-fluorenone via Bayer-Villiger rearrangement reaction;

[0111] S3: Deuterated 2,7-dibromodiol was prepared from deuterated 2,7-dibromolactone by Grignard reaction;

[0112] S4: Deuterated 2,7-dibromodiol reacts with 1-bromooctane to undergo an alkyl substitution reaction at the 4-position alcohol hydroxyl group to obtain an oily transparent solid product;

[0113] S5: using the oily transparent solid product as a raw material, preparing a deuterated PODPF monomer;

[0114] S6: preparing the deuterated PODPF monomer into a solution, performing polymerization reaction, activating and refluxing to obtain the deuterated fluorene-based blue light polymer material.

[0115] It can be understood that in view of the insufficient stability of the PODPF material itself and the urgent need to improve the purity of the device luminescent color, the present invention first uses silver carbonate as a catalyst and heavy water as a deuterium source to deoxygenate 2,7-dibromo-9-fluorenone and directly exchange H / D in one step to synthesize the deuterated raw material, which solves the problem of multiple steps in deuterated synthesis and prepares a new main chain fully deuterated poly 4-alkoxy-9,9-diphenylfluorene polymer luminescent material (d 15 -PODPF), which can be used to prepare planar conformation films, solving the problems of high planar conformation content generated by PODPF annealing and strong interchain aggregation that reduce the blue light color purity and fluorescence quantum efficiency.

[0116] Deuterated fluorene-based blue light polymer material is a conjugated structure with a fully deuterated main chain.

[0117] According to some embodiments of the present invention, in step S1:

[0118] The CAS number of cyclohexyldiphenylphosphine is 6372-42-5.

[0119] Deuterated 2,7-dibromo-9-fluorenone was prepared in a borosilicate glass tube equipped with a magnetic stir bar.

[0120] The preparation process can be repeated multiple times, such as 3 times, and the deuteration rate is about 93%.

[0121] The raw material input in the deuteration reaction can be 1 mmol, and the reaction is repeated three times.

[0122] The preparation method in step S1 adopts Yamamoto reaction.

[0123] Acetone was used as the solvent for polymer purification.

[0124] In combination with the first aspect, in some embodiments of the present invention, in step S2, trifluoroacetic acid and sodium percarbonate are added during the Bayer-Villiger rearrangement reaction.

[0125] In combination with the first aspect, in some embodiments of the present invention, in step S2, the Baeyer-Villiger rearrangement reaction is carried out at room temperature.

[0126] In combination with the first aspect, in some embodiments of the present invention, in step S2, the time of the Baeyer-Villiger rearrangement reaction is 60 to 80 hours.

[0127] In combination with the first aspect, in some embodiments of the present invention, in step S2, the time of the Baeyer-Villiger rearrangement reaction is 70 to 80 hours.

[0128] In combination with the first aspect, in some embodiments of the present invention, in step S2, the time of the Baeyer-Villiger rearrangement reaction is 72 hours.

[0129] In combination with the first aspect, in some embodiments of the present invention, in step S3, the solvent of the grout reaction includes toluene.

[0130] In combination with the first aspect, in some embodiments of the present invention, in step S3, the format reaction is carried out under a protective atmosphere.

[0131] In combination with the first aspect, in some embodiments of the present invention, in step S3, the protective atmosphere includes nitrogen.

[0132] In combination with the first aspect, in some embodiments of the present invention, in step S3, the reaction temperature is 80-90°C.

[0133] In combination with the first aspect, in some embodiments of the present invention, in step S3, the reaction temperature is 85°C.

[0134] In combination with the first aspect, in some embodiments of the present invention, in step S3, the reaction time is 20 hours to 30 hours.

[0135] In combination with the first aspect, in some embodiments of the present invention, in step S3, the reaction time is 24 hours.

[0136] In combination with the first aspect, in some embodiments of the present invention, in step S3, the amount of the Grignard reagent added in the Grignard reaction is 4 to 6 times the equivalent of deuterated 2,7-dibromolactone.

[0137] In combination with the first aspect, in some embodiments of the present invention, in step S4, the alkyl substitution reaction is carried out under alkaline conditions.

[0138] In combination with the first aspect, in some embodiments of the present invention, in step S4, the solvent for the alkyl substitution reaction is acetone.

[0139] In combination with the first aspect, in some embodiments of the present invention, in step S4, the amount of 1-bromooctane added is 1 to 2 times the equivalent of the deuterated 2,7-dibromodiol.

[0140] In combination with the first aspect, in some embodiments of the present invention, in step S4, the amount of 1-bromooctane added is 1.5 times the equivalent of the deuterated 2,7-dibromodiol.

[0141] In the present invention, 1-bromooctane is added, and the corresponding structure is a straight chain. If it is a branched chain, it is impossible to regulate the planar conformation. The branched chain structure can only regulate the spherulite structure (tertiary structure). However, the present invention regulates the planar conformation, that is, the secondary structure.

[0142] In combination with the first aspect, in some embodiments of the present invention, in step S4, the alkyl substitution reaction is carried out at room temperature.

[0143] In combination with the first aspect, in some embodiments of the present invention, in step S4, the time of the alkyl substitution reaction is 20 to 30 hours.

[0144] In combination with the first aspect, in some embodiments of the present invention, in step S4, the time of the alkyl substitution reaction is 24 hours.

[0145] In combination with the first aspect, in some embodiments of the present invention, in step S5, a deuterated PODPF monomer is prepared by a Friedel-Crafts reaction.

[0146] In combination with the first aspect, in some embodiments of the present invention, in step S5, a deuterated PODPF monomer is prepared by Friedel-Crafts reaction, and the specific process is that the product of the previous step is dissolved in anhydrous dichloromethane and reacted under boron trifluoride-ether catalysis conditions for 2 hours to obtain the obtained product.

[0147] In combination with the first aspect, in some embodiments of the present invention, in step S6, the specific process may be:

[0148] Take equal amounts of bipyridine and nickel catalyst Ni(COD)2 in a Shrek flask filled with N2, then activate in a DMF solution at 75°C for 20 minutes, then add a monomer solution dissolved in toluene, reflux at 85°C for 3 days, then cap with 0.1mL dry deuterated bromobenzene, and use a silicon-based metal remover to remove residual nickel catalyst in the post-treatment process. Use DCM as the mobile phase and purify the organic phase with Al2O3 column chromatography, then concentrate the reaction solution, precipitate with anhydrous methanol, and finally use acetone Soxhlet extraction and washing for 3 days to obtain a polymer, which is then vacuum dried to obtain d 15 -PODPF yellow solid is poly 4-alkoxy-9,9-diphenylfluorene polymer luminescent material (M n =31747, n=69).

[0149] Among them, equal amounts of bipyridine and nickel catalyst Ni(COD)2 are used as catalysts to promote the reaction in the positive direction, avoiding the rapid quenching of the catalyst and leading to premature termination of the reaction.

[0150] In combination with the first aspect, in some embodiments of the present invention, in step S6, the reaction time is 1.5 to 4 hours.

[0151] In combination with the first aspect, in some embodiments of the present invention, in step S6, activation is performed in a DMF solution.

[0152] In combination with the first aspect, in some embodiments of the present invention, in step S6, a monomer solution dissolved in toluene is added during the reflux process.

[0153] In combination with the first aspect, in some embodiments of the present invention, in step S6, the reaction is capped with dry deuterated bromobenzene after reflux.

[0154] The specific preparation method of the deuterated fluorenyl polymer is as follows: the fluorenone raw material required for the reaction is deuterated and substituted in one step, and then a straight-chain fluorenyl monomer with a side chain of 8 carbon atoms is synthesized for polymerization. The mass ratio of bipyridine and Ni(COD)2 is 1:1. After activation in a DMF solution at 75°C for 20 minutes, a monomer solution dissolved in toluene is added. After reflux and light-proof reaction at 85°C for 3 days, 0.1 mL of dry deuterated bromobenzene solvent is injected to terminate the reaction (12 hours), and the target polymer is obtained after purification.

[0155] The purification adopts Soxhlet extraction method, and the solvent is acetone. Taking advantage of the difference in solubility between oligomers and polymers in acetone, the oligomers are quickly eluted to achieve the purpose of purification.

[0156] The preparation route of the poly 4-alkoxy-9,9-diphenylfluorene polymer luminescent material of the present invention is as follows:

[0157]

[0158] In the molecular formula, x and y represent the number of monomer units of two different bonding modes, the number of units is a positive integer, and n is the number of structural monomers, which is a positive integer; the number of structural monomers ranges from 25 to 80, and the molecular weight of the polymer is 20,000 to 50,000.

[0159] The poly 4-alkoxy-9,9-diphenylfluorene polymer luminescent material of the present invention is a conjugated fluorene-based polymer material, and the main chain structure is a fully deuterated structure. The fully deuterated structure can significantly reduce the molecular chain vibration frequency of the material, improve the luminescence stability and luminescence efficiency of the material, and facilitate the regulation of the planar conformation. The material synthesis adopts a one-step reaction, the catalyst is silver carbonate, and the deuterium source is heavy water. The polymerization reaction is a Yamamoto reaction, the catalyst is equal amounts of bipyridine and Ni(COD)2, the end-capping agent is deuterated bromobenzene, and it is carried out in a light-proof and oxygen-free atmosphere.

[0160] In the second aspect, some embodiments of the present invention provide a deuterated fluorene-based blue light polymer material, which is prepared by the preparation method of the first aspect of the present invention.

[0161] The deuterated fluorene-based blue light polymer material of the present invention has at least the following beneficial effects:

[0162] Better stability: The CD bond of deuterated materials has higher stability than the CH bond, which reduces the risk of degradation of photosensitive materials during operation, thereby extending the service life of optoelectronic devices.

[0163] Higher luminescence efficiency: Enhancing spin-orbit coupling through the "heavy atom effect" helps to improve the quantum efficiency of the luminescent molecules, thereby improving the overall light output of the device.

[0164] Better spectral purity: Deuteration treatment can reduce non-radiative deactivation pathways in luminescent materials, improve the color purity of blue light emission, and ensure that the device can emit more accurate blue light.

[0165] A more simplified synthesis process: heavy water is used as the deuterium source, and the deuterated raw material is synthesized in a one-step method, which simplifies the synthesis steps, reduces production costs and time, and improves synthesis efficiency.

[0166] Can promote coplanar conformation: The prepared deuterated PODPF material can effectively promote the formation of coplanar conformation, enhance the electroluminescent properties of the material, and reduce the spectral drift caused by interchain aggregation.

[0167] Able to enhance mechanical flexibility: The conjugated skeleton structure of polyfluorene material gives it good mechanical flexibility, making the prepared film have better adaptability and durability in practical applications.

[0168] In the third aspect, some embodiments of the present invention provide a planar conformational film, the preparation raw materials of which include the deuterated fluorene-based blue light polymer material of the second aspect of the present invention.

[0169] It can be understood that the planar conformation film containing deuterated fluorene-based blue light polymer material has many beneficial effects, mainly including:

[0170] The planar conformation helps to improve the electroluminescence efficiency of the material, reduce interchain aggregation and non-radiative energy loss, and thus increase the luminescence intensity and quantum efficiency.

[0171] The film exhibits improved spectral stability under light and heat environments, ensuring consistency of spectral characteristics over long-term use.

[0172] The use of deuterated materials reduces the generation of impurities during the light-emitting process and improves the color purity of blue light emission, meeting the requirements of high-quality displays and lighting equipment.

[0173] Due to the conjugated structure of polyfluorene, the film has a certain mechanical flexibility and is suitable for applications in various flexible electronic devices.

[0174] The planarized conformation can be achieved at a lower annealing temperature, which reduces the thermal impact on the substrate and is suitable for the processing of heat-sensitive materials.

[0175] The thin film material of the present invention can be prepared by a simple solution method, the process is relatively simple, and it is convenient for large-scale production.

[0176] Due to its excellent optoelectronic properties, this thin film material can be widely used in organic light-emitting diodes (OLEDs), solar cells and other optoelectronic devices.

[0177] The planar conformation film of the present invention has an absorption peak shoulder at about 436-440 nm and fluorescence characteristic peaks at 448 nm and 478 nm.

[0178] In a fourth aspect, some embodiments of the present invention provide a method for preparing a planar conformational film according to the third aspect of the present invention, comprising the steps of coating a solution containing the deuterated fluorene-based blue light polymer material on a substrate surface and then annealing the solution.

[0179] By directly coating the deuterated fluorene-based blue light polymer material solution on the surface of the substrate, the complicated processing steps are reduced and the production efficiency is improved.

[0180] The coating process can form a uniform film, improve the performance consistency of optoelectronic devices, and ensure that the light-emitting properties are evenly distributed across the film.

[0181] The annealing process can promote the rearrangement of the molecular chains, making them more planar, thereby improving the electroluminescent performance and stability.

[0182] Annealing helps to remove solvent residues, improve the overall density of the film, and enhance its spectral stability under working conditions.

[0183] According to some embodiments of the present invention, the method for preparing a planar conformational film may be:

[0184] Weigh different masses of polymer powder, place in a 1.5 mL clean sample bottle, add 1 mL of solvent, stir at 60 ° C for 30 min, wait for the polymer powder to completely dissolve, and obtain polymer chloroform solutions of different concentrations;

[0185] A quartz plate with a side length of 1.5 cm is used as a substrate. The quartz base is first cleaned with solvents such as acetone and dichloromethane. 45 microliters of polymer chloroform solution is taken and evenly coated on the quartz substrate using a spin coater (or doctor blade) to obtain a thin film for preparing a planar conformation.

[0186] The above-mentioned film is placed on a heating table. The original film is placed on a heating table. By adjusting the annealing temperature (higher than 200° C.), a series of planar conformation films with different contents can be obtained.

[0187] In the method for preparing a planar conformation film, the thermal annealing temperature is 180°C to 340°C.

[0188] In the method for preparing a planar conformation film, the thermal annealing temperature is 200°C to 280°C.

[0189] The film described in S3 is regulated to have different contents of planar conformation by thermal annealing.

[0190] Properly increasing the temperature is conducive to the material approaching its glass transition temperature, improving the activity of the film's molecular chains, and is more conducive to the formation of a planar conformation. Adjusting the annealing temperature can regulate the content of the planar conformation in the film.

[0191] The specific method is: place the film described in S3 on a heating table at 200°C, in a nitrogen atmosphere (or air atmosphere), heat for about 5 minutes, and cool to room temperature to obtain a fluorene-based polymer film with a slight planar conformation.

[0192] In the method for preparing the planar conformation film, chloroform is selected as the solvent, and the solution concentration is 6-10 mg / mL. The fluorene-based polymer material has a large solubility in chloroform, and different concentrations are conducive to preparing films of different thicknesses.

[0193] The film is prepared by spin coating and scraping process. Compared with the casting film forming method, spin coating and scraping film are smoother.

[0194] The film spin coating speed was 1000 rpm, the acceleration was 800 rpm / s, the scraping speed was 5 mm / s, and the duration was 10 s.

[0195] The preparation method is as follows: taking a quartz sheet of 1.5 cm × 1.5 cm as the substrate, taking 45 microliters of the above solution, adjusting the speed of the coating machine to 1000 rpm, the acceleration to 800 rpm / s, and the duration to 60 s, to obtain a deuterated fluorene-based polymer film. Taking a quartz sheet of 1 cm × 1 cm as the substrate, taking 20 microliters of the above solution, adjusting the scraper speed to 5 mm / s, and the duration to 10 s, to obtain a fluorene-based polymer film.

[0196] Polymer films with different thicknesses and smooth surfaces can be obtained.

[0197] The preparation method of the present invention utilizes the stability of CD bonds and large-sized deuterium atoms to improve the planarization of the main chain, thereby realizing rapid batch preparation of fluorene-based films with planar conformations, improving the ability to form planar conformations in fluorene-based films, improving blue light luminescence efficiency and stability, and solving the problem of reduced luminescence efficiency of films with planar conformations formed in common fluorene-based polymer materials.

[0198] In a fifth aspect, some embodiments of the present invention provide use of the planarized conformational film of the fourth aspect of the present invention in an organic thin film optoelectronic device.

[0199] Applying the planar conformation film prepared from deuterated fluorene-based blue light polymer materials to organic thin film optoelectronic devices can bring the following beneficial effects:

[0200] Improved luminescence efficiency: Since the planar conformation reduces interchain aggregation and non-radiative energy loss, it can significantly increase the luminescence intensity and quantum efficiency in organic light-emitting diodes (OLEDs), thereby improving the overall optoelectronic performance.

[0201] Enhanced spectral stability: The film exhibits good spectral stability under light and heat environments, which helps maintain the consistency of the spectral characteristics of the device over a long period of time, ensuring display quality and service life.

[0202] Improve color purity: The introduction of deuterated materials reduces the generation of impurities during the light-emitting process and improves the color purity of blue light emission, meeting the requirements of high-quality displays and lighting equipment and ensuring accurate color reproduction.

[0203] Mechanical flexibility: The conjugated structure of polyfluorene gives the film a certain mechanical flexibility, making it suitable for use in various flexible electronic devices, expanding its application range.

[0204] Low temperature processing adaptability: The planarized conformation can be achieved at a lower annealing temperature, which reduces the thermal impact on the substrate, is suitable for the processing of heat-sensitive materials, and expands the types of compatible substrates.

[0205] Simplified preparation process: The film is prepared by a simple solution method, which has a relatively simple process and is easy to mass produce, reducing production costs and time.

[0206] Potential for wide application: Due to its excellent optoelectronic properties, this thin film material can be widely used in OLED, solar cells and other optoelectronic devices, promoting the advancement of related technologies and market applications.

[0207] According to some embodiments of the present invention, the organic thin film optoelectronic device includes an organic light emitting diode, an organic field effect transistor, an organic thin film laser, and an organic spin valve.

[0208] Organic light-emitting diodes (OLEDs) are electronic devices that use organic materials to emit light. They work by causing the organic layer to emit light through the flow of electric current. The main advantages include:

[0209] High color quality: enables rich color expression and high contrast.

[0210] Thin, light and flexible: It can produce ultra-thin and flexible displays suitable for various electronic devices.

[0211] Wide viewing angle: Color and brightness remain stable even at extreme viewing angles.

[0212] Low energy consumption: Compared with traditional LCD displays, OLEDs are more energy efficient.

[0213] Organic field effect transistor (OFET) is a field effect transistor based on organic materials, mainly used for switching and amplifying signals. Its advantages include:

[0214] Plasticity: Can be made into flexible electronic devices, suitable for wearable devices and folding screens.

[0215] Low cost: The production process is simple and suitable for large-scale manufacturing.

[0216] Higher mobility: In some organic materials, the mobility of electrons and holes can reach high levels, supporting high-performance devices.

[0217] Organic thin film lasers are lasers based on organic materials that use organic semiconductors to emit light under stimulated radiation. Its features include:

[0218] Low threshold excitation: Compared with inorganic lasers, organic lasers generally have lower threshold excitation energy.

[0219] Diversified colors: By selecting different organic materials, laser output in a variety of colors can be achieved.

[0220] Flexible and lightweight: suitable for a variety of applications, including portable devices and wearable devices.

[0221] Organic spin valve is a device that combines spin electronics and organic materials to achieve information processing by manipulating electron spin. Its features include:

[0222] Low power consumption: The characteristics of spin transport can significantly reduce power consumption and is suitable for high-performance electronic devices.

[0223] Flexible applications: Due to the flexibility of organic materials, they can be integrated into devices of various shapes.

[0224] New functionalities: Combining the properties of spin and charge can enable the development of new types of memory and logic devices.

[0225] These devices have broad application prospects in modern electronic technology, especially in the fields of flexible electronics, wearable technology and high-efficiency display.

[0226] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0227] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0228] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0229] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0230] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0231] Example 1

[0232] First, a deuterated fluorene-based blue light polymer material was prepared, and then a planar conformation film was prepared, as follows:

[0233] S1. Preparation of deuterated 2,7-dibromo-9-fluorenone (1) in a borosilicate glass tube equipped with a magnetic stirring bar:

[0234] 1mmol 2,7-dibromo-9-fluorenone, 0.2mmol silver carbonate, 0.5mmol cyclohexyldiphenylphosphine, 1mmol potassium carbonate, 20mmol heavy water and 0.2mL toluene were placed in a sealed tube, the reaction temperature was adjusted to 120°C, and the reaction was terminated after stirring for 24 hours. The sealed tube was taken out and the temperature was waited to drop to room temperature. Subsequently, saturated ammonium chloride solution was added to the high boron glass sealed tube to quench the reaction, and separation extraction was performed. The obtained organic extract was dried over anhydrous magnesium sulfate and concentrated in a rotary evaporator to obtain a crude product.

[0235] Subsequently, the mixture was purified by silica gel column chromatography using petroleum ether: dichloromethane (2:1) as the eluent to obtain a yellow powder. The above steps were repeated 3 times, and the deuteration rate was about 93%. Note: Do not use a large amount, the best reaction amount is 1mmol (338mg of fluorenone), do not add too much toluene, about 0.2mL is more appropriate, otherwise it will affect the deuteration rate (fluorenone is difficult to dissolve, it will dissolve after heating and stirring, but not all of it will dissolve).

[0236] 2.8 g of deuterated 2,7-dibromo-9-fluorenone (8.28 mmol) (1) was placed in a reaction bottle, and 30 mL of dichloromethane was injected to dissolve it under ice-water bath conditions, and 25 mL of trifluoroacetic acid was injected. 1.0 g of sodium percarbonate was added every 15 minutes for a total of 5 times, and then the ice-water bath was removed. After stirring the reaction at room temperature for 72 hours, the reaction was terminated. Subsequently, the residual trifluoroacetic acid was removed with a saturated sodium bicarbonate aqueous solution, and the aqueous phase was washed with dichloromethane to obtain an organic extract, which was dried with anhydrous magnesium sulfate and evaporated and concentrated in a rotary evaporator to obtain a crude product.

[0237] The product was purified by silica gel column chromatography using petroleum ether: dichloromethane (4:1) as the eluent to obtain deuterated 2,7-dibromolactone as a white powder (2).

[0238] Next, 12 mL of deuterated bromobenzene, 72.4 mmol of magnesium chips (1.8 g), and one iodine particle were placed in a reaction flask, eluted with N2 three times, and tetrahydrofuran was injected under an ice-water bath until the magnesium chips reacted completely to obtain a gray Grignard reagent (3).

[0239] 12mmol of deuterated 2,7-dibromolactone (4.2g) (2) was placed in a three-necked flask, sealed and eluted with N2 three times, 60mL of anhydrous toluene and Grignard reagent were injected, refluxed at 85°C for 8 hours, cooled to room temperature, quenched with saturated aqueous ammonium chloride solution, washed with dichloromethane to obtain an organic extract, dried with anhydrous magnesium sulfate, and evaporated and concentrated in a rotary evaporator to obtain a crude product. The crude product was first purified by silica gel column using petroleum ether: dichloromethane (2:1) and then petroleum ether: ethyl acetate (6:1) as eluent to obtain a white solid of deuterated 2,7-dibromodiol (4).

[0240] Subsequently, 4 mmol (4), 7.2 mmol anhydrous potassium carbonate and 7.8 mmol n-octane bromide were placed in an eggplant-shaped bottle, 30 mL acetone was injected to dissolve, and the mixture was reacted at room temperature for 12 hours.

[0241] Extraction, washing, drying and concentration give a crude product, which is purified by silica gel column with petroleum ether: dichloromethane = 8:1 as eluent to obtain an oily transparent solid (5). Dissolve it in anhydrous dichloromethane, then inject about 0.2 mL of boron trifluoride ether, stir at room temperature for 24 hours, and quench the reaction with 5 mL of water. Washing, extraction, drying and concentration give a crude product, which is then eluted with petroleum ether: dichloromethane (3:1), purified by silica gel column chromatography to obtain a white solid (6) of deuterated PODPF monomer.

[0242] The target polymer was prepared in a 10 mL Shrek flask equipped with a magnetic stir bar. 15-PODPF(7): 0.5 g of bipyridine and Ni(COD)2 were placed in a Shrek tube, eluted with N2 three times, activated in a 75°C DMF solution for 20 min, and then injected with a monomer solution dissolved in a dry, oxygen-free toluene solvent. The reaction temperature was adjusted to 85°C, and the reaction was refluxed in the dark for 3 days. Then, 0.1 mL of dry deuterated bromobenzene was injected to terminate the reaction for 12 hours. After the reaction was completed, the residual reactants were removed by suction filtration using a Buchner funnel to obtain a filament of the target polymer. The residual nickel catalyst was removed by a silicon-based metal scavenger, and the organic phase was purified by Al2O3 column chromatography using dichloromethane as the mobile phase. Then, the reaction solution was concentrated, and anhydrous methanol was added to precipitate to obtain a filamentous yellow solid. After extraction with acetone Soxhlet for 3 days, the solid was dried in a vacuum to obtain d 15 -PODPF yellow solid (M n =31747, n=69).

[0243] S2. Weigh 10 mg of polymer, place it in a 1.5 mL clean sample bottle, add 1 mL of chloroform solvent, stir at 60°C for 30 min, wait for the polymer to be completely dissolved, and obtain a polymer chloroform solution with a concentration of 10 mg / mL.

[0244] S3. Use a quartz sheet with a side length of 1.5 cm as the substrate. First clean the quartz substrate with solvents such as acetone and dichloromethane. Adjust the speed of the spin coater to 1000 rpm and the acceleration to 800 rpm / s. Take 45 microliters of polymer chloroform solution and evenly coat it on the quartz substrate using the spin coater to obtain a thin film with a thickness of 55 nanometers.

[0245] S4. Place the original film on a heating table, adjust the annealing temperature to 200° C., heat for 10 minutes, and obtain a film with a planar conformation content of about 6%.

[0246] Example 2

[0247] First, a deuterated fluorene-based blue light polymer material was prepared, and then a planar conformation film was prepared, as follows:

[0248] S1. Preparation of deuterated 2,7-dibromo-9-fluorenone (1) in a boron glass sealed tube equipped with a magnetic stirring bar: 1mmol 2,7-dibromo-9-fluorenone, 0.2mmol silver carbonate, 0.5mmol cyclohexyldiphenylphosphine, 1mmol potassium carbonate, 20mmol heavy water and 0.2mL toluene were placed in a sealed tube, the reaction temperature was adjusted to 120°C, the reaction was terminated after stirring for 24 hours, the sealed tube was removed and the temperature was allowed to drop to room temperature, then saturated ammonium chloride solution was added to the boron glass sealed tube to quench the reaction, and liquid separation and extraction were performed. The obtained organic extract was dried over anhydrous magnesium sulfate and concentrated in a rotary evaporator to obtain a crude product. Subsequently, the product was purified by silica gel column chromatography using petroleum ether: dichloromethane (2:1) as the eluent to obtain a yellow powder. The above steps were repeated 3 times, and the deuteration rate was about 93%. Note: Do not use a large amount, the best reaction amount is 1mmol (338mg of fluorenone), do not add too much toluene, about 0.2mL is more appropriate, otherwise it will affect the deuteration rate of the material (fluorenone is difficult to dissolve, it will dissolve after heating and stirring but not completely dissolve).

[0249] 2.8 g of deuterated 2,7-dibromo-9-fluorenone (8.28 mmol) (1) was placed in a reaction bottle. Under ice-water bath conditions, 30 mL of dichloromethane was injected to dissolve it, and 25 mL of trifluoroacetic acid was injected. 1.0 g of sodium percarbonate was added every 15 minutes for a total of 5 times. Then the ice-water bath was removed and the reaction was stirred at room temperature for 72 hours before the reaction was terminated. Subsequently, the residual trifluoroacetic acid was removed with a saturated sodium bicarbonate aqueous solution, and the extracted aqueous phase was washed with dichloromethane to obtain an organic extract, which was dried over anhydrous magnesium sulfate and concentrated in a rotary evaporator to obtain a crude product. The deuterated 2,7-dibromolactone was purified by silica gel column chromatography using petroleum ether: dichloromethane (4:1) as the eluent to obtain a white powder (2) of deuterated 2,7-dibromolactone. Then, 12 mL of deuterated bromobenzene, 72.4 mmol of magnesium chips (1.8 g), and iodine particles (one particle) were placed in a reaction bottle, eluted with N2 three times, and tetrahydrofuran was injected under an ice-water bath until the magnesium chips reacted completely to obtain a gray Grignard reagent (3). 12 mmol of deuterated 2,7-dibromolactone (4.2 g) (2) was placed in a three-necked flask, sealed and eluted with N2 three times, and 60 mL of anhydrous toluene and Grignard reagent were injected. After reflux reaction at 85°C for 8 hours, it was cooled to room temperature, quenched with saturated ammonium chloride aqueous solution, and the aqueous phase was washed with dichloromethane to obtain an organic extract, dried with anhydrous magnesium sulfate, and evaporated and concentrated in a rotary evaporator to obtain a crude product. The crude product was first purified by silica gel column using petroleum ether: dichloromethane (2:1) and then petroleum ether: ethyl acetate (6:1) as eluents to obtain a white solid of deuterated 2,7-dibromodiol (4). Subsequently, 4mmol (4), 7.2mmol anhydrous potassium carbonate and 7.8mmol bromooctane were placed in an eggplant-shaped bottle, 30mL acetone was injected to dissolve, and the mixture was reacted at room temperature for 12 hours. The crude product was extracted, washed, dried and concentrated to obtain a crude product, which was purified by silica gel column using petroleum ether: dichloromethane = 8:1 as the eluent to obtain an oily transparent solid (5). The crude product was dissolved in anhydrous dichloromethane, and then about 0.2mL of boron trifluoride ether was injected. After stirring at room temperature for 24 hours, the reaction was quenched with 5mL water. The crude product was washed, extracted, dried and concentrated to obtain a crude product, which was then eluted with petroleum ether: dichloromethane (3:1) and purified by silica gel column chromatography to obtain a white solid (6) of deuterated PODPF monomer.

[0250] The target polymer was prepared in a 10 mL Shrek flask equipped with a magnetic stir bar. 15-PODPF(7): 0.5 g of bipyridine and Ni(COD)2 were placed in a Shrek tube, eluted with N2 three times, activated in a 75°C DMF solution for 20 min, and then injected with a monomer solution dissolved in a dry, oxygen-free toluene solvent. The reaction temperature was adjusted to 85°C, and the reaction was refluxed in the dark for 3 days. Then, 0.1 mL of dry deuterated bromobenzene was injected to terminate the reaction for 12 hours. After the reaction was completed, the residual reactants were removed by suction filtration using a Buchner funnel to obtain a filament of the target polymer. The residual nickel catalyst was removed by a silicon-based metal scavenger, and the organic phase was purified by Al2O3 column chromatography using dichloromethane as the mobile phase. Then, the reaction solution was concentrated, and anhydrous methanol was added to precipitate to obtain a filamentous yellow solid. After extraction with acetone Soxhlet for 3 days, the solid was dried in a vacuum to obtain d 15 -PODPF yellow solid (M n =31747, n=69).

[0251] S2. Weigh 10 mg of polymer, place it in a 1.5 mL clean sample bottle, add 1 mL of chloroform solvent, stir at 60°C for 30 min, wait for the polymer to be completely dissolved, and obtain a polymer chloroform solution with a concentration of 6 mg / mL.

[0252] S3. Use a quartz sheet with a side length of 1.5 cm as the substrate. First clean the quartz substrate with solvents such as acetone and dichloromethane. Adjust the speed of the spin coater to 1000 rpm and the acceleration to 800 rpm / s. Take 45 microliters of polymer chloroform solution and evenly coat it on the quartz substrate using the spin coater to obtain a thin film with a thickness of 45 nanometers.

[0253] S4. Place the original film on a heating table, adjust the annealing temperature to 220° C., and heat for 10 minutes to obtain a film with a planar conformation content of about 24%.

[0254] Example 3

[0255] First, a deuterated fluorene-based blue light polymer material was prepared, and then a planar conformation film was prepared, as follows:

[0256] S1. Preparation of deuterated 2,7-dibromo-9-fluorenone (1) in a boron glass sealed tube equipped with a magnetic stirring bar: 1mmol 2,7-dibromo-9-fluorenone, 0.2mmol silver carbonate, 0.5mmol cyclohexyldiphenylphosphine, 1mmol potassium carbonate, 20mmol heavy water and 0.2mL toluene were placed in a sealed tube, the reaction temperature was adjusted to 120°C, the reaction was terminated after stirring for 24 hours, the sealed tube was removed and the temperature was allowed to drop to room temperature, then saturated ammonium chloride solution was added to the boron glass sealed tube to quench the reaction, and liquid separation and extraction were performed. The obtained organic extract was dried over anhydrous magnesium sulfate and concentrated in a rotary evaporator to obtain a crude product. Subsequently, the product was purified by silica gel column chromatography using petroleum ether: dichloromethane (2:1) as the eluent to obtain a yellow powder. The above steps were repeated 3 times, and the deuteration rate was about 93%. Note: Do not use a large amount, the best reaction amount is 1mmol (338mg of fluorenone), do not add too much toluene, about 0.2mL is more appropriate, otherwise it will affect the deuteration rate of the material (fluorenone is difficult to dissolve, it will dissolve after heating and stirring but not completely dissolve).

[0257] 2.8 g of deuterated 2,7-dibromo-9-fluorenone (8.28 mmol) (1) was placed in a reaction bottle. Under ice-water bath conditions, 30 mL of dichloromethane was injected to dissolve it, and 25 mL of trifluoroacetic acid was injected. 1.0 g of sodium percarbonate was added every 15 minutes for a total of 5 times. Then the ice-water bath was removed and the reaction was stirred at room temperature for 72 hours before the reaction was terminated. Subsequently, the residual trifluoroacetic acid was removed with a saturated sodium bicarbonate aqueous solution, and the extracted aqueous phase was washed with dichloromethane to obtain an organic extract, which was dried over anhydrous magnesium sulfate and concentrated in a rotary evaporator to obtain a crude product. The deuterated 2,7-dibromolactone was purified by silica gel column chromatography using petroleum ether: dichloromethane (4:1) as the eluent to obtain a white powder (2) of deuterated 2,7-dibromolactone. Then, 12 mL of deuterated bromobenzene, 72.4 mmol of magnesium chips (1.8 g), and iodine particles (one particle) were placed in a reaction bottle, eluted with N2 three times, and tetrahydrofuran was injected under an ice-water bath until the magnesium chips reacted completely to obtain a gray Grignard reagent (3). 12 mmol of deuterated 2,7-dibromolactone (4.2 g) (2) was placed in a three-necked flask, sealed and eluted with N2 three times, and 60 mL of anhydrous toluene and Grignard reagent were injected. After reflux reaction at 85°C for 8 hours, it was cooled to room temperature, quenched with saturated ammonium chloride aqueous solution, and the aqueous phase was washed with dichloromethane to obtain an organic extract, dried with anhydrous magnesium sulfate, and evaporated and concentrated in a rotary evaporator to obtain a crude product. The crude product was first purified by silica gel column using petroleum ether: dichloromethane (2:1) and then petroleum ether: ethyl acetate (6:1) as eluents to obtain a white solid of deuterated 2,7-dibromodiol (4). Subsequently, 4mmol (4), 7.2mmol anhydrous potassium carbonate and 7.8mmol bromooctane were placed in an eggplant-shaped bottle, 30mL acetone was injected to dissolve, and the mixture was reacted at room temperature for 12 hours. The crude product was extracted, washed, dried and concentrated to obtain a crude product, which was purified by silica gel column using petroleum ether: dichloromethane = 8:1 as the eluent to obtain an oily transparent solid (5). The crude product was dissolved in anhydrous dichloromethane, and then about 0.2mL of boron trifluoride ether was injected. After stirring at room temperature for 24 hours, the reaction was quenched with 5mL water. The crude product was washed, extracted, dried and concentrated to obtain a crude product, which was then eluted with petroleum ether: dichloromethane (3:1) and purified by silica gel column chromatography to obtain a white solid (6) of deuterated PODPF monomer.

[0258] The target polymer was prepared in a 10 mL Shrek flask equipped with a magnetic stir bar. 15-PODPF(7): 0.5 g of bipyridine and Ni(COD)2 were placed in a Shrek tube, eluted with N2 three times, activated in a 75°C DMF solution for 20 min, and then injected with a monomer solution dissolved in a dry, oxygen-free toluene solvent. The reaction temperature was adjusted to 85°C, and the reaction was refluxed in the dark for 3 days. Then, 0.1 mL of dry deuterated bromobenzene was injected to terminate the reaction for 12 hours. After the reaction was completed, the residual reactants were removed by suction filtration using a Buchner funnel to obtain a filament of the target polymer. The residual nickel catalyst was removed by a silicon-based metal scavenger, and the organic phase was purified by Al2O3 column chromatography using dichloromethane as the mobile phase. Then, the reaction solution was concentrated, and anhydrous methanol was added to precipitate to obtain a filamentous yellow solid. After extraction with acetone Soxhlet for 3 days, the solid was dried in a vacuum to obtain d 15 -PODPF yellow solid (M n =31747, n=69).

[0259] S2. Weigh 10 mg of polymer, place it in a 1.5 mL clean sample bottle, add 1 mL of chloroform solvent, stir at 60°C for 30 min, wait for the polymer to be completely dissolved, and obtain a polymer chloroform solution with a concentration of 6 mg / mL.

[0260] S3. Use a quartz sheet with a side length of 1.5 cm as the substrate. First clean the quartz substrate with solvents such as acetone and dichloromethane. Adjust the speed of the spin coater to 1000 rpm and the acceleration to 800 rpm / s. Take 45 microliters of polymer chloroform solution and evenly coat it on the quartz substrate using the spin coater to obtain a thin film with a thickness of 45 nanometers.

[0261] S4. Place the original film on a heating table, adjust the annealing temperature to 240° C., and heat for 10 minutes to obtain a film with a planar conformation content of about 32%.

[0262] Comparative Example 1

[0263] First, a fluorene-based polymer material PODPF with a conjugated structure was prepared, and then a film was prepared, as follows:

[0264] S1. Preparation of fluorene-based polymer material PODPF with conjugated structure by Yamamoto polymerization.

[0265] The preparation method is:

[0266] Take 2.8g 2,7-dibromo-9-fluorenone (8.28mmol) and place it in a reaction bottle. In an ice-water bath, inject 30mL of dichloromethane to dissolve it, inject 25mL of trifluoroacetic acid, add 1.0g of sodium percarbonate every 15 minutes, for a total of 5 times, then remove the ice-water bath, stir and react at room temperature for 72 hours, and then end the reaction. Subsequently, remove the residual trifluoroacetic acid with a saturated sodium bicarbonate aqueous solution, wash the extracted aqueous phase with dichloromethane to obtain an organic extract, dry it with anhydrous magnesium sulfate, and evaporate and concentrate it in a rotary evaporator to obtain a crude product. Use petroleum ether: dichloromethane (4:1) as the eluent and purify it by silica gel column chromatography to obtain 2,7-dibromolactone as a white powder. Then take 12mL bromobenzene, 72.4mmol magnesium chips (1.8g), and iodine particles (one particle) in the reaction bottle, elute three times, and inject tetrahydrofuran under an ice-water bath until the magnesium chips react completely to obtain a gray Grignard reagent. 12mmol of 2,7-dibromolactone (4.2g) was placed in a three-necked flask, sealed and eluted three times, 60mL of anhydrous toluene and Grignard reagent were injected, refluxed at 85℃ for 8 hours, cooled to room temperature, quenched with saturated aqueous ammonium chloride solution, washed with dichloromethane to obtain an organic extract, dried with anhydrous magnesium sulfate, and evaporated and concentrated in a rotary evaporator to obtain a crude product. The crude product was first purified by silica gel column with petroleum ether: dichloromethane (2:1) and then petroleum ether: ethyl acetate (6:1) as eluent to obtain a white solid of 2,7-dibromodiol. Subsequently, 4mmol 2,7-dibromodiol, 7.2mmol anhydrous potassium carbonate and 7.8mmol bromooctane were placed in an eggplant-shaped flask, 30mL of acetone was injected to dissolve, and the reaction was carried out at room temperature for 12 hours. Extraction, washing, drying and concentration were performed to obtain a crude product, which was purified by silica gel column with petroleum ether: dichloromethane = 8:1 as eluent to obtain an oily transparent solid. It was dissolved in anhydrous dichloromethane, and then injected with about 0.2 mL of boron trifluoride ether, stirred at room temperature for 24 hours, and then quenched with 5 mL of water. The crude product was washed, extracted, dried and concentrated, and then eluted with petroleum ether: dichloromethane (3:1), and purified by silica gel column chromatography to obtain a white solid of PODPF monomer.

[0267] The target polymer PODPF was prepared in a 10 mL Shrek flask equipped with a magnetic stirring bar: 0.5 g of bipyridine and Ni(COD)2 were taken into a Shrek tube, eluted with N2 three times, activated in a 75°C DMF solution for 20 min, and then injected with a monomer solution dissolved in a dry, oxygen-free toluene solvent. The reaction temperature was adjusted to 85°C, and refluxed for 3 days in the dark, and then 0.1 mL of dry bromobenzene was injected to terminate the reaction for 12 hours. After the reaction was completed, the residual reactants were removed by suction filtration with a Buchner funnel to obtain a filament of the target polymer, and the residual nickel catalyst was removed by a silicon-based metal scavenger. The organic phase was purified by Al2O3 column chromatography using dichloromethane as the mobile phase, and then the reaction solution was concentrated, anhydrous methanol was added to precipitate to obtain a filamentous yellow solid, which was extracted with acetone Soxhlet for 3 days and then vacuum dried to obtain a yellow solid PODPF (M n =54812, n=123).

[0268] The structure of the prepared fluorene-based polymer material PODPF with a conjugated structure is shown below:

[0269]

[0270] S2. Weigh 10 mg of polymer, place it in a 1.5 mL clean sample bottle, add 1 mL of chloroform solvent, stir at 60°C for 30 min, wait for the polymer to be completely dissolved, and obtain a polymer chloroform solution with a concentration of 10 mg / mL.

[0271] S3. Use a quartz sheet with a side length of 1.5 cm as the substrate. First clean the quartz substrate with solvents such as acetone and dichloromethane. Adjust the speed of the spin coater to 1000 rpm and the acceleration to 800 rpm / s. Take 45 microliters of polymer chloroform solution and evenly coat it on the quartz substrate using the spin coater to obtain a thin film with a thickness of 55 nanometers.

[0272] S4. Placing the above film on a heating platform. The original film is placed on a heating platform, and the annealing temperature is adjusted to 200° C. and heated for 10 minutes. No planar conformation is formed.

[0273] The reason why the planarized conformation was not formed in Comparative Example 1 was that the temperature was not reached.

[0274] Comparative Example 2

[0275] First, a fluorene-based polymer material PODPF with a conjugated structure was prepared, and then a film was prepared, as follows:

[0276] S1. Preparation of fluorene-based polymer material PODPF with conjugated structure by Yamamoto polymerization.

[0277] The preparation method is:

[0278] Take 2.8g 2,7-dibromo-9-fluorenone (8.28mmol) and place it in a reaction bottle. In an ice-water bath, inject 30mL of dichloromethane to dissolve it, inject 25mL of trifluoroacetic acid, add 1.0g of sodium percarbonate every 15 minutes, for a total of 5 times, then remove the ice-water bath, stir and react at room temperature for 72 hours, and then end the reaction. Subsequently, remove the residual trifluoroacetic acid with a saturated sodium bicarbonate aqueous solution, wash the extracted aqueous phase with dichloromethane to obtain an organic extract, dry it with anhydrous magnesium sulfate, and evaporate and concentrate it in a rotary evaporator to obtain a crude product. Use petroleum ether: dichloromethane (4:1) as the eluent and purify it by silica gel column chromatography to obtain 2,7-dibromolactone as a white powder. Then take 12mL bromobenzene, 72.4mmol magnesium chips (1.8g), and iodine particles (one particle) in the reaction bottle, elute three times, inject tetrahydrofuran under an ice-water bath, until the magnesium chips react completely to obtain a gray Grignard reagent. 12mmol of 2,7-dibromolactone (4.2g) was placed in a three-necked flask, sealed and eluted three times, 60mL of anhydrous toluene and Grignard reagent were injected, refluxed at 85℃ for 8 hours, cooled to room temperature, quenched with saturated aqueous ammonium chloride solution, washed with dichloromethane to obtain an organic extract, dried with anhydrous magnesium sulfate, and evaporated and concentrated in a rotary evaporator to obtain a crude product. The crude product was first purified by silica gel column with petroleum ether: dichloromethane (2:1) and then petroleum ether: ethyl acetate (6:1) as eluent to obtain a white solid of 2,7-dibromodiol. Subsequently, 4mmol 2,7-dibromodiol, 7.2mmol anhydrous potassium carbonate and 7.8mmol bromooctane were placed in an eggplant-shaped flask, 30mL of acetone was injected to dissolve, and the reaction was carried out at room temperature for 12 hours. Extraction, washing, drying and concentration were performed to obtain a crude product, which was purified by silica gel column with petroleum ether: dichloromethane = 8:1 as eluent to obtain an oily transparent solid. It was dissolved in anhydrous dichloromethane, and then injected with about 0.2 mL of boron trifluoride ether, stirred at room temperature for 24 hours, and then quenched with 5 mL of water. The crude product was washed, extracted, dried and concentrated, and then eluted with petroleum ether: dichloromethane (3:1), and purified by silica gel column chromatography to obtain a white solid of PODPF monomer.

[0279] The target polymer PODPF was prepared in a 10 mL Shrek flask equipped with a magnetic stirring bar: 0.5 g of bipyridine and Ni(COD)2 were taken into a Shrek tube, eluted with N2 three times, activated in a 75°C DMF solution for 20 min, and then injected with a monomer solution dissolved in a dry, oxygen-free toluene solvent. The reaction temperature was adjusted to 85°C, and refluxed for 3 days in the dark, and then 0.1 mL of dry bromobenzene was injected to terminate the reaction for 12 hours. After the reaction was completed, the residual reactants were removed by suction filtration with a Buchner funnel to obtain a filament of the target polymer, and the residual nickel catalyst was removed by a silicon-based metal scavenger. The organic phase was purified by Al2O3 column chromatography using dichloromethane as the mobile phase, and then the reaction solution was concentrated, anhydrous methanol was added to precipitate to obtain a filamentous yellow solid, which was extracted with acetone Soxhlet for 3 days and then vacuum dried to obtain a yellow solid PODPF (M n =54812, n=123).

[0280] The structure of the prepared fluorene-based polymer material PODPF with a conjugated structure is shown below:

[0281]

[0282] S2. Weigh 10 mg of polymer, place it in a 1.5 mL clean sample bottle, add 1 mL of chloroform solvent, stir at 60°C for 30 min, wait for the polymer to be completely dissolved, and obtain a polymer chloroform solution with a concentration of 10 mg / mL.

[0283] S3. Use a quartz sheet with a side length of 1.5 cm as the substrate. First clean the quartz substrate with solvents such as acetone and dichloromethane. Adjust the speed of the spin coater to 1000 rpm and the acceleration to 800 rpm / s. Take 45 microliters of polymer chloroform solution and evenly coat it on the quartz substrate using the spin coater to obtain a thin film with a thickness of 55 nanometers.

[0284] S4. Place the original film on a heating table, adjust the annealing temperature to 220° C., heat for 10 minutes, and form a film with a planar conformation of about 11%.

[0285] Comparative Example 3

[0286] S1. Preparation of fluorene-based polymer material PODPF with conjugated structure by Yamamoto polymerization.

[0287] The preparation method is:

[0288] Take 2.8g 2,7-dibromo-9-fluorenone (8.28mmol) and place it in a reaction bottle. In an ice-water bath, inject 30mL of dichloromethane to dissolve it, inject 25mL of trifluoroacetic acid, add 1.0g of sodium percarbonate every 15 minutes, for a total of 5 times, then remove the ice-water bath, stir and react at room temperature for 72 hours, and then end the reaction. Subsequently, remove the residual trifluoroacetic acid with a saturated sodium bicarbonate aqueous solution, wash the extracted aqueous phase with dichloromethane to obtain an organic extract, dry it with anhydrous magnesium sulfate, and evaporate and concentrate it in a rotary evaporator to obtain a crude product. Use petroleum ether: dichloromethane (4:1) as the eluent and purify it by silica gel column chromatography to obtain 2,7-dibromolactone as a white powder. Then take 12mL bromobenzene, 72.4mmol magnesium chips (1.8g), and iodine particles (one particle) in the reaction bottle, elute three times, inject tetrahydrofuran under an ice-water bath, until the magnesium chips react completely to obtain a gray Grignard reagent. 12mmol of 2,7-dibromolactone (4.2g) was placed in a three-necked flask, sealed and eluted three times, 60mL of anhydrous toluene and Grignard reagent were injected, refluxed at 85℃ for 8 hours, cooled to room temperature, quenched with saturated aqueous ammonium chloride solution, washed with dichloromethane to obtain an organic extract, dried with anhydrous magnesium sulfate, and evaporated and concentrated in a rotary evaporator to obtain a crude product. The crude product was first purified by silica gel column with petroleum ether: dichloromethane (2:1) and then petroleum ether: ethyl acetate (6:1) as eluent to obtain a white solid of 2,7-dibromodiol. Subsequently, 4mmol 2,7-dibromodiol, 7.2mmol anhydrous potassium carbonate and 7.8mmol bromooctane were placed in an eggplant-shaped flask, 30mL of acetone was injected to dissolve, and the reaction was carried out at room temperature for 12 hours. Extraction, washing, drying and concentration were performed to obtain a crude product, which was purified by silica gel column with petroleum ether: dichloromethane = 8:1 as eluent to obtain an oily transparent solid. It was dissolved in anhydrous dichloromethane, and then injected with about 0.2 mL of boron trifluoride ether, stirred at room temperature for 24 hours, and then quenched with 5 mL of water. The crude product was washed, extracted, dried and concentrated, and then eluted with petroleum ether: dichloromethane (3:1), and purified by silica gel column chromatography to obtain a white solid of PODPF monomer.

[0289] The target polymer PODPF was prepared in a 10 mL Shrek flask equipped with a magnetic stirring bar: 0.5 g of bipyridine and Ni(COD)2 were taken into a Shrek tube, eluted with N2 three times, activated in a 75°C DMF solution for 20 min, and then injected with a monomer solution dissolved in a dry, oxygen-free toluene solvent. The reaction temperature was adjusted to 85°C, and refluxed for 3 days in the dark, and then 0.1 mL of dry bromobenzene was injected to terminate the reaction for 12 hours. After the reaction was completed, the residual reactants were removed by suction filtration with a Buchner funnel to obtain a filament of the target polymer, and the residual nickel catalyst was removed by a silicon-based metal scavenger. The organic phase was purified by Al2O3 column chromatography using dichloromethane as the mobile phase, and then the reaction solution was concentrated, anhydrous methanol was added to precipitate to obtain a filamentous yellow solid, which was extracted with acetone Soxhlet for 3 days and then vacuum dried to obtain a yellow solid PODPF (M n =54812, n=123).

[0290] The structure of the prepared fluorene-based polymer material PODPF with a conjugated structure is shown below:

[0291]

[0292] S2. Weigh 10 mg of polymer, place it in a 1.5 mL clean sample bottle, add 1 mL of chloroform solvent, stir at 60°C for 30 min, wait for the polymer to be completely dissolved, and obtain a polymer chloroform solution with a concentration of 10 mg / mL.

[0293] S3. Use a quartz sheet with a side length of 1.5 cm as the substrate. First clean the quartz substrate with solvents such as acetone and dichloromethane. Adjust the speed of the spin coater to 1000 rpm and the acceleration to 800 rpm / s. Take 45 microliters of polymer chloroform solution and evenly coat it on the quartz substrate using the spin coater to obtain a thin film with a thickness of 55 nanometers.

[0294] S4. Place the original film on a heating table, adjust the annealing temperature to 240° C., heat for 10 minutes, and form a film with a planar conformation of about 18%.

[0295] It should be noted that although comparative examples 2 and 3 also formed thin films with planar conformations, the difference from the embodiments is that the main chain deuteration increases the size of the molecular chain aggregates and makes the aggregates more densely packed, which is conducive to the formation of a planar conformation. Therefore, the temperature for forming a planar conformation will be lowered.

[0296] Test analysis

[0297] Figure 1 The UV-visible absorption spectra and fluorescence emission spectra of the original fluorene-based polymer film obtained in Example 1 and Comparative Example 1 of the present invention and after heat treatment are shown in FIG. Figure 1It can be seen that the absorption and emission spectra of the PODPF film are available. The UV spectrum of the film annealed at 200°C has no obvious change, and the peak intensity of the PL spectrum at 460nm (0-1 peak) increases slightly, indicating that the annealing temperature is not enough to induce the conformational transition of the PODPF molecular chain. 15 -PODPF film post-treatment, comparison of luminescence spectra shows that when the annealing temperature is 200℃, d 15 The UV spectrum of -PODPF has a weak absorption peak at 438nm, indicating that the transition from random conformation to planar conformation is induced at this temperature, which also confirms that main chain deuteration can improve the ability of PODPF to form a planar conformation.

[0298] Figure 2 The UV-visible absorption spectra and fluorescence emission spectra of the original fluorene-based polymer film obtained in Example 2 and Comparative Example 2 of the present invention and after heat treatment are shown in FIG. Figure 2 It can be seen that when the thermal annealing temperature increases to 220 °C, the PODPF film and d 15 -PODPF films all formed a planar conformation, and compared with the PODPF film, the content of the conformation in the deuterated film was higher than that in the non-deuterated film.

[0299] Figure 3 The UV-visible absorption spectra and fluorescence emission spectra of the original fluorene-based polymer film obtained in Example 3 and Comparative Example 3 of the present invention and after heat treatment are shown in FIG. Figure 3 It can be seen that when the thermal annealing temperature increases to 240 °C, the PODPF film and d 15 -PODPF films all formed a planar conformation, and compared with the PODPF film, the content of the conformation in the deuterated film was higher than that in the non-deuterated film.

[0300] Figure 4 The lifespan diagram of the original fluorene-based polymer film obtained in Example 123 of the present invention and Comparative Example 123 and after heat treatment is shown in FIG. Figure 4 It can be seen that d 15 The overall life of the -PODPF film is higher than that of the PODPF film, and the trends of their lifespan changes with temperature are opposite.

[0301] Figure 5 It is a structural diagram of a fluorene-based polymer thin film device with a planar conformation obtained in Example 1 of the present invention and Comparative Example 1, and the device structure is ITO / PEDOT:PSS / EML / TPBi / LiF / Al.

[0302] Figure 6 is a performance diagram of the fluorene-based polymer thin film device with a planar conformation obtained in Example 1 of the present invention and Comparative Example 1, from Figure 6It can be seen that compared with the device based on PODPF as the light-emitting layer in Comparative Example 1, the device based on the deuterated thin film emits dark blue light. As the device operates, it exhibits a more stable color purity and still emits dark blue light after working for 2 hours.

[0303] Figure 7 is the H NMR spectrum of the polymer synthesized in Example 1 of the present invention, from Figure 7 It can be seen that the characteristic peak of hydrogen on the benzene ring in the high-field position of NMR is almost non-existent, proving that d 15 -PODPF material was successfully prepared.

[0304] Figure 8 is the GPC test of the synthesized polymer in Example 1 of the present invention, from Figure 8 It can be seen that the polymer PDI curve is a sharp peak, indicating that the molecular weight of the polymer is relatively uniform.

[0305] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing a deuterated fluorene-based blue light polymer material, characterized in that: The following steps are involved: S1: Deuterated 2,7-dibromo-9-fluorenone was prepared using 2,7-dibromo-9-fluorenone as raw material, silver carbonate and cyclohexyldiphenylphosphine as catalysts, and heavy water as a deuterium source; S2: Preparation of deuterated 2,7-dibromolactone from deuterated 2,7-dibromo-9-fluorenone via Bayer-Villiger rearrangement reaction; S3: Deuterated 2,7-dibromodiol was prepared from deuterated 2,7-dibromolactone by Grignard reaction; S4: Deuterated 2,7-dibromodiol reacts with 1-bromooctane to undergo an alkyl substitution reaction at the 4-position alcohol hydroxyl group to obtain an oily transparent solid product; S5: using the oily transparent solid product as a raw material, preparing a deuterated PODPF monomer; S6: preparing the deuterated PODPF monomer into a solution, performing polymerization reaction, activating and refluxing to obtain the deuterated fluorene-based blue light polymer material.

2. The preparation method according to claim 1, characterized in that: In step S2, during the Bayer-Villiger rearrangement reaction, trifluoroacetic acid and sodium percarbonate are added; and / or, in step S2, the Bayer-Villiger rearrangement reaction is carried out at room temperature; and / or, in step S2, the Bayer-Villiger rearrangement reaction time is 60 to 80 hours.

3. The preparation method according to claim 1, characterized in that: In step S3, the solvent of the Grignard reaction includes toluene; and / or, in step S3, the Grignard reaction is carried out under a protective atmosphere; and / or, in step S3, the reaction temperature is 80 to 90° C.; and / or, in step S3, the reaction time is 20 h to 30 h; and / or, in step S3, the amount of Grignard reagent added in the Grignard reaction is 4 to 6 times the equivalent of deuterated 2,7-dibromolactone.

4. The preparation method according to claim 1, characterized in that: In step S4, the amount of 1-bromooctane added is 1 to 2 times the equivalent of the deuterated 2,7-dibromodiol; and / or, in step S4, the alkyl substitution reaction is carried out at room temperature; and / or, in step S4, the time of the alkyl substitution reaction is 20 to 30 hours.

5. The preparation method according to claim 1, characterized in that: In step S5, a deuterated PODPF monomer is prepared by Friedel-Crafts reaction.

6. The preparation method according to claim 1, characterized in that: In step S6, the polymerization reaction time is 1.5 to 4 hours; and / or, in step S6, activation is carried out in a DMF solution; and / or, in step S6, a monomer solution dissolved in toluene is added during the reflux process; and / or, in step S6, dry deuterated bromobenzene is used for end-capping after reflux.

7. A deuterated fluorene-based blue light polymer material, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. A planar conformation film, characterized in that: The preparation raw materials include the deuterated fluorene-based blue light polymer material as described in claim 7.

9. A method for preparing a planar conformational film as claimed in claim 8, characterized in that: The method comprises the steps of coating a solution containing the deuterated fluorene-based blue light polymer material on the surface of a substrate and then annealing the solution.

10. Use of the planar conformational film according to claim 8 in an organic thin film optoelectronic device.

Citation Information

Patent Citations

  • Preparation of novel 9,9-diaryl fluorene polymer photoelectric functional material and photoelectric device application

    CN106866939A

  • Deuterated composition, organic light-emitting device and display device

    WO2023165398A1